Study Tentang Model Fuzzy Goal Programming Pada Pendekatan Masalah Perencanaan Produksi - Desi Vinsensia; Yulia Utami; Mian Sari Simanjuntak; Arya Riski Tarigan (Institute of Computer Science (IOCS), 2021)
The production planning system can provide satisfaction to the manufacture with the desire target and also with the available raw materials. In achieving the target of goals also face a situation of uncertainty (fuzzy). The aims of this study is proposed the model of fuzzy goal programming approach to optimize production planning system. In this model obtaining maximizing profit and revenue with consider minimize costs of labor cost, raw materials cost, time machine production, and also inventory cost. The numerical example is illustrate that the fuzzy goal programming model can optimize optimize production and profit according desired of decision maker.